2020
DOI: 10.1111/jth.14756
|View full text |Cite
|
Sign up to set email alerts
|

C‐terminal residues of activated protein C light chain contribute to its anticoagulant and cytoprotective activities

Abstract: Background: Activated protein C (APC) is an important homeostatic blood coagulation protease that conveys anticoagulant and cytoprotective activities. Proteolytic inactivation of factors Va and VIIIa facilitated by cofactor protein S is responsible for APC's anticoagulant effects, whereas cytoprotective effects of APC involve primarily the endothelial protein C receptor (EPCR), protease activated receptor (PAR)1 and PAR3.Objective: To date, several binding exosites in the protease domain of APC have been ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…We reported reduced anti-inflammatory of the APC mutant, as demonstrated by enhanced leukocyte recruitment and adhesion, higher endothelial permeability, and altered gene expression profiles. These results corroborate with the previous findings that not only the reduced anticoagulant activity but also impaired cytoprotective effect of the variant promote thrombogenesis [ 14 , 15 ]. Furthermore, we also demonstrated impaired anti-apoptotic capacity of the K150del variant, which played an important role for nerve repair in IS [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We reported reduced anti-inflammatory of the APC mutant, as demonstrated by enhanced leukocyte recruitment and adhesion, higher endothelial permeability, and altered gene expression profiles. These results corroborate with the previous findings that not only the reduced anticoagulant activity but also impaired cytoprotective effect of the variant promote thrombogenesis [ 14 , 15 ]. Furthermore, we also demonstrated impaired anti-apoptotic capacity of the K150del variant, which played an important role for nerve repair in IS [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
“…Diminished anticoagulant activity and cytoprotective effects of certain APC variants can greatly increase the risk of thrombosis, especially when the vascular endothelium is inflamed or mechanically damaged [ 24 ]. For instance, the K150del variant is associated with an increased risk of venous thromboembolism and IS due to impaired anticoagulant activity and endothelial barrier protection effect [ 12 15 ]. We reported reduced anti-inflammatory of the APC mutant, as demonstrated by enhanced leukocyte recruitment and adhesion, higher endothelial permeability, and altered gene expression profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study showed that R189W of PC had normal amidolytic and proteolytic activities in the absence of cofactors but exhibited ~ 3 times lower affinity for binding to endothelial protein C receptor, while K193del of PC had normal amidolytic and proteolytic activities in the absence of cofactors but exhibited ~ 2–3-fold impaired anticoagulant activity in the presence of PS in vitro [ 17 ]. In 2020, Yamashita et al stressed the functional importance of six residues within G184-L197 of PC (R185, K188, R189, K192, K193 and R194) on constituting activated protein C (APC)’s anticoagulant and cytoprotective activities [ 25 ]. According to their study, mutations at residue K192 or K193 exhibited 50% reduced APC’s anticoagulant activity with a decreased sensitivity for PS and reduced cytoprotective activities with an impaired ability to cleave PAR cleavage, while other residues including R189 presented similar APC’s anticoagulant activity and cytoprotective activities to wide-type APC [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…After cleavage, before tethered ligand binding to PAR1 to activate it, the PAR1 N-terminus interacts with the light chain of APC in two regions: C-terminus including Lys-150 and Lys-151 (59), and EGF-like domain 1 of APC (60). We modeled these interactions using several approaches: in the first approach, the PAR1 N- terminal peptide fragments were docked to APC using the flexible peptide docking method (29); the second approach included folding of PAR1 and EPCR-APC as heterotrimer with AlphaFold software; and the third approach was MD simulation of the system containing APC and PAR1 N-terminus.…”
Section: Structure Function and Dynamics Of Apc Epcr Apc-epcr Complexmentioning
confidence: 99%